Carbon Stock and Soil Characteristics under Expansive Shrubs in the Dry Afromontane Forest in Northern Ethiopia - Mebrahtu Haile; Emiru Birhane; Meley Mekonen Rannestad; Muyiwa S. Adaramola (International Journal of Forestry Research)
Increased presence of expansive plant species could bring about various ecological influences on biomass carbon, soil organic carbon, and the physical and chemical properties of the soils. However, their impacts on these ecological parameters could differ due to a wide range of life forms, plant communities of the invaded ecosystems, and abiotic conditions. This work was conducted to examine the impacts of Cadia purpurea and Tarchonanthus camphoratus cover on carbon stock in vegetation and soil and soil physicochemical properties in Desa’a forest, northern Ethiopia. Vegetation and soil data were collected from a total of 150 sampling plots (size 20 m × 20 m) from uninvaded and invaded vegetation conditions. The soil samples were collected from topsoil (0–15 and 15–30 cm) of the uninvaded and invaded vegetation conditions. The statistical difference in carbon stock and soil characteristics P<0.05 of both invaded and uninvaded vegetation conditions were tested using an independent t-test using an R-software. The mean above- and below-ground biomass carbon stocks of the uninvaded vegetation condition (17.62 Mg·C/ha and 4.14 Mg·C/ha, respectively) were found to be significantly higher than those of the invaded vegetation condition (4.73 Mg·C/ha and 1.11 Mg·C/ha, respectively). The mean soil organic carbons (SOC) were significantly higher P<0.01 in the uninvaded (122.83 Mg·C/ha) than in the invaded (90.13 Mg·C/ha) vegetation condition. The total carbon stock estimates were significantly higher P<0.01 in the uninvaded vegetation condition (144.59 Mg·C/ha) than in the invaded vegetation condition (95.97 Mg·C/ha). Furthermore, the result revealed that most of the soil characteristics were significantly lower P<0.05 under the expansive shrubs invaded vegetation conditions except for significantly high sand content P<0.05. Silt, nitrogen, phosphorus, calcium, copper, and zinc did not significantly change with the cover of the expansive shrubs. Our results suggest that increased presence of the expansive species decreased carbon trapping and affected most of the soil nutrients within the forest. Hence, to enhance the carbon storage potential and to maintain the soil nutrient status of the forest, proper conservation, monitoring, and management of the existing PNV and controlling a further expansion of the expansive shrubs are required. Further studies will be required on the factors responsible for the difference in carbon stocks and soil nutrients in each vegetation condition in addition to the impacts of the expansive shrubs expansion.